Relationship between Governance and Economic Growth - Adhikari, Gyan Mani (Damak Campus Journal, 2024)
Governance and economic growth are interconnected with each other. A sound understanding of good governance and economic growth plays a critical role in solving the existing debatable issues of whether economic growth drives good governance or good governance drives economic growth. The study employed the co-integration test and Granger causality test to examine the relationship between governance indicators, developed by the World Bank, through the government efficiency index (GEI) and real gross domestic product using time series data for the period 2002–2022. The VECM results showed that there exists a long-run relationship between CIM and real GDP. Based on VECM test results, the study concluded that all the explanatory variables have a short-run relationship with economic growth at a 1 percent level of significance. The Granger causality test result indicates that causality runs from the government effective index as well as government expenditure to real GDP in the short run. The study recommended that governments or policymakers should widen their focus on integration between institutional factors and economic variables that affect economic growth.